2015
DOI: 10.1111/gbi.12139
|View full text |Cite
|
Sign up to set email alerts
|

In situ trace metal analysis of Neoarchaean – Ordovician shallow‐marine microbial‐carbonate‐hosted pyrites

Abstract: Pre-Cambrian atmospheric and oceanic redox evolutions are expressed in the inventory of redox-sensitive trace metals in marine sedimentary rocks. Most of the currently available information was derived from deep-water sedimentary rocks (black shale/banded iron formation). Many of the studied trace metals (e.g. Mo, U, Ni and Co) are sensitive to the composition of the exposed land surface and prevailing weathering style, and their oceanic inventory ultimately depends on the terrestrial flux. The validity of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 131 publications
(251 reference statements)
2
9
0
Order By: Relevance
“…Hence, these data provide insight into the small degrees of redox change that led, perhaps in fits and starts, to full oceanic oxygenation. A Cryogenian–Ediacaran increase in oxygenation agrees with other redox-sensitive elements 10 62 63 and biomarker evidence 64 . Thus, the significance of the Se isotope record is not only that it adds to growing evidence that the late Proterozoic and Cambrian ocean and atmosphere reached a progressively more oxic state, coinciding with the diversification of animal life, but also that the process of oxidation was protracted, and not ultimately triggered by the Gaskiers deglaciation, as other data suggest 5 .…”
Section: Discussionsupporting
confidence: 70%
“…Hence, these data provide insight into the small degrees of redox change that led, perhaps in fits and starts, to full oceanic oxygenation. A Cryogenian–Ediacaran increase in oxygenation agrees with other redox-sensitive elements 10 62 63 and biomarker evidence 64 . Thus, the significance of the Se isotope record is not only that it adds to growing evidence that the late Proterozoic and Cambrian ocean and atmosphere reached a progressively more oxic state, coinciding with the diversification of animal life, but also that the process of oxidation was protracted, and not ultimately triggered by the Gaskiers deglaciation, as other data suggest 5 .…”
Section: Discussionsupporting
confidence: 70%
“…The use of the pyrite records has recently found support in the work of Gallagher et al (2015) who reported a suite of trace element data (Mo, Ni, As, Co, Zn) from Precambrian to Ordovician carbonate-hosted pyrite deposited in shallow marine environments. Their data were centered on the Archean-…”
Section: Sedimentary To Early Diagenetic Pyritementioning
confidence: 89%
“…The resulting tuffs are present above and below SrKu34 (Figure ) and these have been used for U/Pb zircon geochronology (e.g., Sumner & Bowring, ), providing strong evidence for relatively proximal, explosive volcanism from evolved magmas (that permitted crystallisation of zircon), possibly in the adjacent “Hamersley” arc‐retro arc system (Zeh et al., ). Finally, there is evidence that the Gamohaan basin was sulphate‐limited; not only is the range in δ 34 S limited (Domagal‐Goldman, Kasting, Johnston, & Farquhar, ; Guo et al., ; Papineau et al., ; Whitehouse, ) but several Gamohaan Formation spheroidal pyrites also preserve δ 34 S isotopic gradients as a function of their spherical segment radius, suggesting a limit on sulphate availability during BSR (Gallagher et al., ; Kamber & Whitehouse, ). Thus, sulphur fallout could easily overwhelm the ambient isotopic signal.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, very delicate microbial kerogen is preserved in exquisite detail in the limestones below the host of SrKu34 (e.g., Kamber et al., ; Sumner, ) and many of these limestones contain intricately distributed micron‐scale pyrite grains with no evidence for dissolution. Furthermore, the pyrite chemistry itself (Gallagher et al., ) as well as the REE systematics of the hosting limestones (e.g., Kamber et al., ) argues strongly in favour of reducing conditions during the Gamohaan Fm. 's deposition and diagenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation